2020
DOI: 10.4314/ijbcs.v14i1.8
|View full text |Cite
|
Sign up to set email alerts
|

Effet aphicide de l’huile essentielle de <i>Ocimum basilicum</i> L. et de son composé majoritaire sur le puceron du cotonnier <i>Aphis gossypii</i> Glover (Homoptera : Aphididae) au Togo

Abstract: L’utilisation abusive des produits chimiques de synthèse pose un problème de santé publique. Afin de contribuer à la protection écologique durables des cultures, les effets aphicides in vitro de l’huile essentielle de Ocimum basilicum L. une plante de la flore togolaise et son composé majoritaire, l’estragole, ont été évalués sur les adultes du puceron Aphis gossypii. Les tests biologiques ont été effectués en laboratoire selon la méthode recommandée par Insecticide Resistance Action Commitee (IRAC) N° 1 Versi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…The results showed an increase in aphid mortality rate with increasing doses of the mixtures used, 24 hours after the release of the aphids on the treated cotton leaves. This direct correlation between aphid mortality rates on the one hand and product concentration on the other hand (in accordance with the classical dose-effect relationship) was similar to those observed in the tests carried out with O. canum and O. basilicum essential oils separately 9,12 . The results also showed that low concentrations of O. canum essential oil mixed with O. basilicum essential oil in higher proportion induced more mortality than the opposite case.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The results showed an increase in aphid mortality rate with increasing doses of the mixtures used, 24 hours after the release of the aphids on the treated cotton leaves. This direct correlation between aphid mortality rates on the one hand and product concentration on the other hand (in accordance with the classical dose-effect relationship) was similar to those observed in the tests carried out with O. canum and O. basilicum essential oils separately 9,12 . The results also showed that low concentrations of O. canum essential oil mixed with O. basilicum essential oil in higher proportion induced more mortality than the opposite case.…”
Section: Discussionsupporting
confidence: 88%
“…Thus, in recent years, much work has been carried out to propose alternative protection methods that respect the environment, such as plant extracts with an insecticidal effect and inert substances 6 . Indeed, studies carried out with the essential oils of certain plants have given effective insecticidal effects on several crop pests [7][8][9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…L'action antifongique des huiles essentielles est de nos jours bien établie. En effet plusieurs travaux ont été réalisés pour l'étude de leurs pouvoirs inhibiteurs dans les domaines médicaux et vétérinaires, sur les champignons pathogènes et les insectes (Alemayehu, 2014;Rosello et al, 2015 ;Wafa et Sofiane, 2020 ;Akantetou et al, 2020). Par ailleurs, au Burkina Faso, la plante entière de Lippia multiflora, de Ocimum basilicum et de Ocimum americanum étaient beaucoup utilisées traditionnellement par les populations comme insectifuges dans les habitations (elles le sont aujourd'hui mais de moins en moins); les rameaux fructifères de Cymbopogon schoenanthus étaient utilisées pour conserver certains produits de récolte (niébé, voandzou, …) dans les sacs.…”
Section: Discussionunclassified
“…Cela s'expliquerait par la qualité et la quantité des molécules antifongiques que renferme chaque huile essentielle et aussi à la structure chimique des molécules (Zarith et al, 2018). Par exemple, l'huile essentielle de Ocimum basilicum est constituée de 24 composés (Akantetou et al, 2020) dont les plus majoritaires sont les monoterpènes oxygénés représentés principalement par l'estragol (38,78%), le linalol (19,45%) et le méthyleugénol (9,98%). Ils sont suivis par le bergamotène (8,48 %) qui est un sesquiterpène hydrocarboné (Ngom et al, 2014).…”
Section: Discussionunclassified
“…Its cultivation is prone to attack by bioaggressors, among whom entomological fauna is one of the most important and difficult to control (Matthews, 1989). In Togo, losses from pest complexes without phytosanitary protection range from 60 to 80% on average (Akantetou, 2014). The geographical extension of this culture, its alternation or association with vegetable and food crops and its genetic improvement have as consequences the evolution of the diversity of the parasitic features with an economic impact of some pests considered as minor a few years ago.…”
Section: Introductionmentioning
confidence: 99%